Heuristic production line balancing problem solution with MATLAB software programming - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2016)
Purpose - The purpose of this paper is to find the most efficient assembly line balancing solution across many heuristic line balancing methods, in assistance with a developed computer program. Design/methodology/approach - In this paper, assembly line balancing problem was analyzed using t-shirt and knitted pants data. A computer program using MATLAB software for the solution of assembly line balancing problems has been developed. In this study, following heuristic assembly line balancing methods were applied: Hoffman method; position weight method; COMSOAL method; and Kilbridge and Wester method. A MATLAB program has been developed by taking into account of theoretical solution of all these methods. Later the program is developed further by analyzing solutions made manually and is made to verify the developed program. Findings - Pre-studies which were conducted in order to decide which programming language would be the best choice for line balancing methods' application came out with the result that MATLAB, from between C, C++, C# and Java, would be the best software choice. The main reason for this choice is that MATLAB is a powerful matrix operation software with a powerful user interface designing tool and has the tools to make development program to be used universally in every computer. Originality/value - When the researches were investigated, it is clearly seen that, this study is the first research on using computer program for solving assembly line balancing problem.
Keywords: MATLAB; COMSOAL method; Heuristic assembly line balancing methods; Hoffman method; Kilbridge and Wester method; Ranked positional weight; APPAREL; TIMES